Modeling of strategic alignment to modify TOGAF architecture development method based on business strategy model - Yoppy Mirza, Maulana; Zafril Rizal, M Azmi; Ruzaini, Abdullah Arshah (Insight Society, 2023)
Strategic alignment is generally seen as an important driver for optimizing business performance. Strategic alignment is aligning internal resource capabilities and external opportunities for superior performance. To realize the suitability of Business and IT strategies, a framework is needed, namely Enterprise Architecture (EA). One of the frameworks for EA is The Open Group Architecture Framework (TOGAF). TOGAF is a method for developing and managing the Enterprise Architecture life cycle called Architectural Development Method (ADM). This ADM integrates elements of the TOGAF standard in responding to the organization's business, and IT needs. In this paper, researchers will contribute to formulating a strategic alignment model to modify the existing strategic alignment in TOGAF ADM based on the business strategy model. In this business model strategy, there are two things: the analysis of business strategy choices and the Balanced Score Card (BSC) strategy map. Analysis of business strategy choices uses SWOT analysis as a business strategy determination based on internal and external business environment analysis. Second, the BSC strategy map is a process of mapping business strategies into the BSC strategy map, which includes four perspectives: financial, customer, internal business processes, and learning and growth perspectives. This model was tested at the Universitas Dinamika, and the results have a good alignment rate of 95%. For further research, this model can be tested in various organizations, such as universities and public and private organizations.